Effect of nonthermal plasma on the properties of a resinous liner submitted to aging - Goiato, Marcelo Coelho [UNESP]; Silva, Emily Vivianne Freitas da [UNESP]; Medeiros, Rodrigo Antonio de [UNESP]; Bitencourt, Sandro Basso [UNESP]; Rangel, Elidiane Cipriano [UNESP]; da Cruz, Nilson Cristino [UNESP]; dos Santos, Daniela Micheline [UNESP] (Elsevier, 2018)
Statement of problem: The properties, such as softness and viscoelasticity, of a resinous reliner can deteriorate and extrinsic elements can become incorporated, making surface protection of the reliner material essential. Purpose: The purpose of this in vitro study was to evaluate the effect of low temperature plasma on Coe-Soft resinous reliner, submitted to aging in artificial saliva for up to 180 days. Sorption, solubility, Shore A hardness, surface energy, and topographic characteristics were analyzed by scanning electronic microscopy (SEM) and energy-dispersive spectroscopy (EDS). Material and methods: Forty-four specimens were fabricated and distributed in 2 groups: nonplasma reliner (control group) and reliner with plasma (plasma group). The plasma was applied with a mixture of 70% hexamethyldisiloxane, 20% O, and 10% Ar. Total work pressure was maintained at a constant 20 Pa for 30 minutes of deposition. The specimens were analyzed before and after aging in an incubator with immersion in artificial saliva for 30, 90, and 180 days. The quantitative data were submitted to 2-way ANOVA and the Tukey test (α=.05), while qualitative data were compared visually. Results: The control group presented lower Shore A hardness values only in the initial period, and surface energy increased with aging for both groups until 90 days. Greater sorption percentage values were encountered at 180 days in the plasma group. Greater solubility values were encountered in the control group in all periods. Conclusions: Plasma is an option for the protection of the material studied because the deposited film remained on the surface of the reliner material after aging.